Respuestas

2013-10-18T00:27:35+02:00
Fernanda,
Vamos a usar la fórmula de Báskara

x = [-b + ó - (raiz delta)]/2a
    delta = b^2 - 4.a.c
          a = - 2 
          b = 5
          c = - 2
                          delta = 5^2 - 4(-2)(-2)
                                  = 25 - 16
                                  = 9                razi delta = 3 ó -3
x = (- 5 + ó - 3)/(-2.2)
   x = ( - 5 - 3)/(-4)                  x1 = 2
   x = (- 5 + 3)/(-4)                  x2 = 1/2           
                                                              S = {1/2, 2}